An exploration of Thai public perceptions of defenses in cases of women who kill their domestically violent spouses - Ho, Robert - (The Australian and New Zealand journal of criminology, 2017)
The present study investigated the issue of domestic violence in Thailand and in particular the reactions of the Thai populace (male versus female) to a battered woman who killed her abusive spouse, as well as how such reactions could be influenced by the presentation of expert testimony related to the battered woman syndrome. Cluster sampling conducted within the Bangkok metropolitan area in Thailand yielded a sample of 1190 participants who voluntarily filled in the study’s questionnaire. Multi-group path analysis showed no significant gender difference in the direct influence of battered woman syndrome information on the verdict/judgment rendered and suggests that the provision of such information in spousal homicide trials within the Thai context may not be efficacious in influencing the participants’ verdict judgments. Results however did indicate an indirect effect of the battered woman syndrome information on the verdict/judgment rendered being mediated by the defense strategy of self-defense. This finding indicated that the battered woman syndrome information presented aided the participants in contextualizing the defendant’s killing in a frame of self-defense, rather than inappropriately applying a form of “reasonableness” in their verdict/judgment. These findings are discussed in relation to their implications for the presentation of battered woman syndrome information in trials of Thai battered women who killed their abusive spouses.